Underdiagnosis of Influenza Virus Infection in Hospitalized Older Adults. Issue 3 (13th February 2018) - Hartman, Lauren; Zhu, Yuwei; Edwards, Kathryn M.; Griffin, Marie R.; Talbot, H. Keipp
Abstract : Objectives: To describe factors associated with provider‐ordered influenza testing in hospitalized older adults. Design: Information on participant demographics, symptoms, and provider‐ordered influenza testing were collected by questionnaire and chart review. We conducted prospective laboratory‐based surveillance using reverse‐transcriptase polymerase chain reaction (RT‐PCR), the criterion standard for diagnosis of influenza, to determine how participant characteristics and provider‐ordered testing affected accurate influenza diagnosis. Setting: One academic and three community hospitals in Davidson County, Tennessee. Participants: Adults aged 18 and older with acute respiratory illness or nonlocalizing fever (N=1, 422). Measurements: We compared characteristics of participants with and without provider‐ordered testing for influenza using the Wilcoxon test and Pearson chi‐square test. Multivariable logistic regression models were used to identify factors predictive of provider‐ordered influenza testing. Results: Twenty‐eight percent (399/1, 422) of participants had provider‐ordered influenza testing. Participants who were tested were younger than those not tested (58 ± 18 vs 66 ± 15, p<.001) and more likely to have influenza‐like illness (ILI) (71% vs 49%, p<.001). ILI decreased with increasing age (aged 18–49, 63%; aged 50–64, 60%; aged ≥65, 48%). ILI and younger age were independent predictors of provider‐ordered testing. Of the 136 participants with influenza confirmed using RT‐PCR, ILI was the only significant predictor of provider‐ordered testing (adjusted odds ratio=3.43, 95% confidence interval=1.22–9.70). Conclusion: Adults aged 65 and older hospitalized with fever or respiratory symptoms during influenza season are less likely to undergo a provider‐ordered influenza test than younger adults. Some, but not all, of this disparity is due to a lower likelihood of ILI. Further strategies are needed to increase clinician awareness and testing in this vulnerable group.